2014
DOI: 10.1111/ijcp.12582
|View full text |Cite
|
Sign up to set email alerts
|

Does mHealth increase adherence to medication? Results of a systematic review

Abstract: Our results showed mixed evidence regarding the benefits of interventions because of the variety of the study designs and the results found. Nevertheless, the interventions do seem to have been beneficial, as 65% of the studies had positive outcomes. Therefore, more high-quality studies should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(128 citation statements)
references
References 47 publications
6
118
2
Order By: Relevance
“…It is also inherently evident that most of the studies reviewed in this paper were undertaken over shorter periods of time (between 2 years and 4 days). Whereas this is a limitation beyond this paper, it is a calling for longitudinal studies and long term programmatic efforts that would provide more detailed evidence [40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…It is also inherently evident that most of the studies reviewed in this paper were undertaken over shorter periods of time (between 2 years and 4 days). Whereas this is a limitation beyond this paper, it is a calling for longitudinal studies and long term programmatic efforts that would provide more detailed evidence [40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…However, another recent systematic review on the same topic supported its conclusions 3. In contrast, a recent Cochrane Review concluded lack of convincing evidence for beneficial effects of medication reminders; specifically among RCTs with the lowest risk of bias 2.…”
Section: Commentarymentioning
confidence: 98%
“…With the surge in mobile phone access globally over the past decade, mobile phonebased interventions have been explored in a wide variety of healthcare interventions, with mixed results (Free et al 2013;Anglada-Martinez et al 2014;Vervloet et al 2012). Furthermore, there is a dearth of high-quality trials with adequate power, and most of the trials that have been conducted have been done so in high-income countries (Free et al 2013;Anglada-Martinez et al 2014;Vervloet et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is a dearth of high-quality trials with adequate power, and most of the trials that have been conducted have been done so in high-income countries (Free et al 2013;Anglada-Martinez et al 2014;Vervloet et al 2012). …”
Section: Introductionmentioning
confidence: 99%